Towards a conceptual-based, student-centred pedagogy: Teacher candidates' experiences of crafting the objects of learning. Issue 4 (3rd October 2019) - , Miechie; Michelle Tan, Yuen Sze; Adler, Douglas J.
Abstract : Purpose: The purpose of this paper is to report on the approaches teacher candidates (TCs) took to craft the object of learning and the critical aspects when applying variation theory, in planning science lessons. It addresses the difficulty TCs often face in determining what students could learn when crafting the objects of learning and the critical aspects. Design/methodology/approach: A total of 27 science TCs from an initial teacher education (ITE) were introduced to variation theory and collaborated in groups of four to five to plan lessons. Data included recordings of the lesson planning session and fieldnotes, TCs' lesson plans and individual semi-structured interviews. Phenomenography as a methodology was employed to capture the variation in the TCs' approaches in crafting the objects of learning and the critical aspects, resulting in categories of description that illustrated the complexity of the lesson planning process the TCs engaged with. Findings: Arranged in hierarchical order, the three categories of description include TCs: analysing content knowledge in order to promote conceptual learning; reflecting on personal experiences and beliefs about teaching and learning; and drawing on external resources to develop knowledge about students. Practical implications: The ways the TCs engaged with lesson planning constituted valuable resources to build their capacity to differentiate between superficial content engagement and deep conceptual learning. Originality/value: The study reports on the potential of framing ITE discourse using variation theory to support TCs' engaging with science teaching that is more conceptual-based, while increasing their sensitivity to students' common conceptions that constrained the learning of canonical science.